Territórios em disputas na Amazônia brasileira: ribeirinhos e camponeses frente as hidrelétricas e ao agronegócio - Ricardo Gilson da Costa Silva; Luís Augusto Pereira Lima; Francilene Sales da Conceição (Confins)
The Brazilian Amazon has become an appropriate space for large hydroelectric projects and expansion of soybean agribusiness, mobilizing national and international companies in search of new areas to transform nature into a commodity. Such geography becomes more complex when the disputed territory reaches traditional communities, which suffer social and territorial pressure from this modeling process on the region. Thus, these processes are analyzed over the riverside communities affected by the Madeira hydroelectric power plants, in Porto Velho (Rondônia), and the communities of small holders living in Belterra and Santarém (Pará). The conclusion is that these social groups have their territories transformed by the expansion of capital in the Amazon, in regions that had not yet been transformed into commodities. It means that traditional Amazonian communities, even inhabiting remote areas in the Amazon, are threatened in their socio-territorial condition.